1992
DOI: 10.1073/pnas.89.23.11367
|View full text |Cite
|
Sign up to set email alerts
|

pH gradients across phospholipid membranes caused by fast flip-flop of un-ionized fatty acids.

Abstract: A central, unresolved question in cell physiology is how fatty acids move across cell membranes and whether protein(s) are required to facilitate transbilayer movement. We have developed a method for monitoring movement of fatty acids across protein-free model membranes (phospholipid bilayers). Pyranin, a water-soluble, pH-sensitive fluorescent molecule, was trapped inside well-sealed phosphatidylcholine vesicles (with or without cholesterol) in Hepes buffer (pH 7.4). Upon addition of a long-chain fatty acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
291
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(322 citation statements)
references
References 30 publications
29
291
0
2
Order By: Relevance
“…Given the rising incidence of obesity and insulin resistance, treatments that target lipid metabolism in the intestine and inhibit intestinal fat absorption are increasingly important. Although fatty acids are hydrophobic and are capable of rapidly diffusing through the lipid bilayer when present in high concentrations [41], a large body of evidence supports the presence of a protein-mediated carrier system that operates at low substrate concentrations [24,42]. I-FABP and FATP4 are thought to be key factors for long-chain fatty acid uptake in enterocytes [24,25], whereas NPC1L1 is thought to play a critical role in intestinal cholesterol absorption [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Given the rising incidence of obesity and insulin resistance, treatments that target lipid metabolism in the intestine and inhibit intestinal fat absorption are increasingly important. Although fatty acids are hydrophobic and are capable of rapidly diffusing through the lipid bilayer when present in high concentrations [41], a large body of evidence supports the presence of a protein-mediated carrier system that operates at low substrate concentrations [24,42]. I-FABP and FATP4 are thought to be key factors for long-chain fatty acid uptake in enterocytes [24,25], whereas NPC1L1 is thought to play a critical role in intestinal cholesterol absorption [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…LCFFA entry into vesicles was paralleled by a decrease in intravesicle pH, suggesting that the LCFFA species that flip-flops across the membrane is the protonated fatty acid (FAH), which then dissociates to the fatty acid anion (FA ؊ ) and a proton. 4 Such studies have been interpreted by some 5 but not all 6 investigators as arguing against the possibility of, or cellular need for, a specific FFA transport process. When the same techniques were used to study LCFFA uptake by living cells, the data suggested much slower flip-flop rates, with a t 1/2 of 60 seconds or more.…”
Section: Commentsmentioning
confidence: 99%
“…The reason is twofold: i) the flip-flop of charged molecules is known to be facilitated by an increase in mechanical tension accompanied by defect formation in at least one leaflet, [22] and ii) the large K p value of long-chain fatty acids predicts such a high transport rate [23] that the differences in P M can hardly be detected with current techniques. [24][25][26] Missner and Pohl Page 2…”
Section: Exceptions To the Meyer-overton Rule Unrelated To The Transimentioning
confidence: 99%